Price premiums, payment delays, and default risk: understanding developing country farmers' decisions to market through a cooperative or a private trader. (6th April 2018) - Saitone, Tina L.; Sexton, Richard J.; Malan, Benoît
Abstract: Smallholder farmers in developing countries face a competitive disadvantage in modern agricultural supply chains. Joint marketing through cooperatives is a potential tool to mitigate these disadvantages; yet cooperatives' success in these settings is uneven at best. We develop an analytical model to study a farmer's choice of selling to a private trader who pays cash on delivery but may exercise market power or a cooperative that promises a price premium but delays payment and carries a concomitant risk of default. In the presence of impatient and risk‐averse farmers, we show that these factors can severely limit smallholder patronage of a cooperative, despite a promised price premium. We then construct and parameterize a simulation model to fit a profile of heterogeneous farmers within a prototype developing‐country village, and study the optimal decisions of farmers regarding marketing through a cooperative versus a private trader. Results suggest that modest improvements in either timeliness of payment or probability of default can induce a substantial increase in a cooperative's market share and economic viability. Extending the simulation analysis to a dynamic setting shows how implementing reasonable policies to improve a cooperative's payment timeliness and default probability can markedly improve its growth trajectory.